The role of organizational culture in mediating the relationship between transformational leadership and organizational innovation: a case of Sana'a University / Ammar Yahya Al-Amri - Al-Amri, Ammar Yahya (2020)
Despite the enormous number of researches of the transformational leadership and organizational innovation in developed nations, there are a few researches in the Arab world especially the Republic of Yemen. This study examines the relationship between transformational leadership and organizational innovation in higher education in Yemen, with organizational culture as a mediator. Transformational leadership has been termed as the most appropriate style of leadership which, when practiced, not only enhances employee morale and motivation, but also leads to enhanced organizational innovativeness. Organizational innovation is a well-researched area. For organizations, innovation is one of the most important factors contributing to competitiveness and differentiation. A quantitative approach was mainly conducted in this study. In order to achieve the main objectives of this study, data were collected from managerial employees from Sana'a University participated in this research in Yemen. Out of the 350 samples, 330 responses (94.29 % response rate) were collected based on random sampling; eventually, 279 responses were usable. The data collected through survey instrument was analyzed using Statistical Package for Social Sciences (SPSS) software Version 21.0; The analysis examined the relationship between the variables of the proposed model, and includes confirmatory factor analysis (CFA), and structural equation modelling (SEM) via AMOS. The results of the analysis show that the data fit the proposed model well, including three second-order constructs; transformational leadership, organizational culture, and organizational innovation. The finding of this study showed that there was significant and positive relationship between transformational leadership and organizational innovation. The findings also indicate that organizational culture has a significant mediating role on the relationship between transformational leadership and organizational innovation. The study is important from the both theoretical and practical perspective especially for practitioner and scholars to refer. The study may contribute to the body of knowledge on the organizational innovation, transformational leadership, and organizational culture perspective. This research has been provided the Sana'a University with important data and insights on current state and practice of transformational leadership and organizational innovation by Sana'a University.